2010
DOI: 10.1177/0731684409347807
|View full text |Cite
|
Sign up to set email alerts
|

Off-axis Crashworthiness Characteristic of Woven Glass/Epoxy Composite Box Structures

Abstract: This study investigates the influence of off-axis loading on the fracture mechanism and specific energy absorption (SEA) of glass/epoxy twill/weave composite box structures. In this regard, the off-axis angles of 5°, 10°, 20°, and 30° of loading direction with respect to the composite box axis is studied experimentally under quasi-static crushing process. At the off-axis angle of 5°, the crushing process behavior is similar to that of the axial crushing and fracture mechanisms, such as bundle fracture and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…However, according to previous studies on axial crushing behaviour and oblique loading [10] [12] [14] [15], at oblique loading, the absorbers could experience an initial peak load followed by catastrophic failure which results into low energy absorption. Extensive studies have concerned with this phenomenon [17] [18] [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to previous studies on axial crushing behaviour and oblique loading [10] [12] [14] [15], at oblique loading, the absorbers could experience an initial peak load followed by catastrophic failure which results into low energy absorption. Extensive studies have concerned with this phenomenon [17] [18] [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the foam filling in a thin-walled tubes increased the amount of energy absorbed compared with empty tubes. Ghasemnejad and Hadavinia [5] have extensively investigated the axial and off-axis crashworthy behavior of CFRP and GFRP composite box structures. In their work, the inclination angles of 5˚, 10˚, 20˚, and 30˚ of loading direction with respect to composite box axis were studied experimentally under quasi-static crushing process.…”
Section: Introductionmentioning
confidence: 99%
“…Progressive failure mode and Figure 9. Comparison of axial and off-axis crushing process, (a) axial crushing and (b) off-axis crushing [143]. Figure 10.…”
Section: Interlaminar Fracture Toughnessmentioning
confidence: 99%
“…In general a tougher matrix result into a higher G IC in composites, this is beneficial in crashworthiness design [138]. Cauchi Savona et al [139] Ghasemnejad et al [142] Ghasemnejad and Hadavinia [143] studied the off-axis crashworthy behaviour of woven GFRP composite box structures. They concluded that two fracture mechanisms of bundle fracture and crack propagation delamination in Mode-II for all composite boxes at various off-axis loading was observed.…”
Section: A Rabiee H Ghasemnejadmentioning
confidence: 99%
See 1 more Smart Citation